2022
DOI: 10.1155/2022/7655142
|View full text |Cite
|
Sign up to set email alerts
|

Naringin protects human nucleus pulposus cells against TNF-α-induced inflammation, oxidative stress, and loss of cellular homeostasis by enhancing autophagic flux via AMPK/SIRT1 activation

Abstract: Activation of the proinflammatory-associated cytokine, tumor necrosis factor-α (TNF-α), in nucleus pulposus (NP) cells is essential for the pathogenesis of intervertebral disc degeneration (IDD). Restoring autophagic flux has been shown to effectively protect against IDD and is a potential target for treatment. The goal of this study was to explore particular autophagic signalings responsible for the protective effects of naringin, a known autophagy activator, on human NP cells. The results showed that signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…Previous studies have shown that autophagy played a protective role against the oxidative stress in degenerative NPCs [ 24 , 30 , 32 ]. In this research, a significantly different autophagy score between NPC/MSC samples and NPC samples was observed ( Figure 6(a) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that autophagy played a protective role against the oxidative stress in degenerative NPCs [ 24 , 30 , 32 ]. In this research, a significantly different autophagy score between NPC/MSC samples and NPC samples was observed ( Figure 6(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation analysis between DElncRNAs and hub OSRDEGs was performed, and DElncRNA-OSRDEG pairs with r > 0.95 and p < 0.05 were selected. The targeted miRNAs for 10 hub OSRDEGs were predicted using TargetScan database ( http://www.targetscan.org/vert_80/ ) [ 30 ]. The targeted miRNAs for DElncRNAs were predicted using the ENCORI database ( https://starbase.sysu.edu.cn/ ) [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fan et al reported that EF-2001 remarkably elevated the expressions of p-AMPK and p-ACC in mice and suggested that EF-2001 decreases hepatic lipid accumulation in the DIO model mice via AMPK pathway while improving livers injured by an HFD [ 23 ]. AMPK is an important factor in regulating homeostasis and basal metabolism in mammalian cells [ 48 ]. The AMPK is a protein marker of lipolysis which demonstrates the effects of drugs that induce lipid production in vivo or in vitro and activates lipolysis enzymes (such as HSL, ATGL, and MGL).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK loss could cooperate with oncogenic divers to accelerate tumorigenesis in a tissue-specific manner [28]. Activated AMPK modulated a variety of metabolic processes, including autophagy [29,30]. Under energy-deprived conditions, AMPK is activated triggering autophagy [31].…”
Section: Discussionmentioning
confidence: 99%